2008
DOI: 10.1016/s1726-4901(08)70150-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment and Falls in the Elderly: The Shihpai Eye Study

Abstract: Falls were significantly associated with a best-corrected Snellen visual acuity of less than 6/12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…Older age[15][16], female gender[16][17], and poorer visual acuity[18][19] were noted as risk factors for falling in previous studies. One study showed that falls were significantly associated with poor visual acuity and higher waist-to-hip ratio [19]. Waist circumference, the indicator of central obesity, is a novel associated factor for falls.…”
Section: Discussionmentioning
confidence: 78%
“…Older age[15][16], female gender[16][17], and poorer visual acuity[18][19] were noted as risk factors for falling in previous studies. One study showed that falls were significantly associated with poor visual acuity and higher waist-to-hip ratio [19]. Waist circumference, the indicator of central obesity, is a novel associated factor for falls.…”
Section: Discussionmentioning
confidence: 78%
“…, 1997). The waist‐to‐hip ratio also has been found to be related significantly to falls (Kuang et al. , 2008) because adipose tissue accumulation and body mass increases can cause a worsening of the balance (Greve et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support that the female gender was a risk factor of falling in elder people. The other factors were the older age and the poor visual acuity that present in elderly women 8 .…”
Section: Differences Of Sexmentioning
confidence: 99%
“…In obesity, the circumference of waist reveals the existence of central obesity and has a major independent role as a fall-related indicator 8 . The existence of central obesity predisposes the development of metabolic syndrome, and at the same time affects the stability of body center and the incidence of fall-related injuries 10 .…”
Section: Obesity and Falling Incidentmentioning
confidence: 99%